PENGGUNAAN MEDIA PEMBELAJARAN POWTOON DALAM UPAYA MENINGKATKAN HASIL BELAJAR SENI RUPA SISWA KELAS VIII-3 SMP PGRI 4 PADANG - Riswalkam Riswalkam; Abd. Hafiz (Serupa The Journal of Art Education, 2020)
The purpose of this study was to improve learning outcomes for drawing comic materials through the use of powtoon learning media in class VIII-3 of SMP PGRI 4 Padang. This type of research is Classroom Action Research with the use of powtoon media in learning. The research results obtained from data processing showed an increase in student learning outcomes. In the first cycle the average student learning outcomes was 77.85, after improvements in the second cycle the average student learning outcomes increased significantly to 86.00. Based on the results of the research above, it can be concluded that the powtoon learning media can improve learning outcomes of fine arts learning material for comic drawing material for students of SMP PGRI 4 Padang.Key Words: Learning Outcomes, Powtoon Learning Media.